2017
DOI: 10.21533/pen.v5i3.122
|View full text |Cite
|
Sign up to set email alerts
|

Combined natural convection and thermal radiation in an inclined cubical cavity with a rectangular pins attached to its active wall

Abstract: Three dimensional combined natural convection and thermal radiation in an inclined cubic enclosure with pins attached to the active wall is investigated numerically. The vertical opposing walls are heated and cooled while the other walls are assumed to be adiabatic. The governing flow, momentum equations and the radiative transfer are solved using Fluent® 6.3 CFD software. In the discretization of the convection terms, the second order upwind scheme and for the solution algorithm SIMPLE is used. The cubic encl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(14 reference statements)
1
0
0
Order By: Relevance
“…It should be noted that the average heat transfer coefficient and Nusselt number profiles shown in Figures 7 and 8 are drawn as dashed lines, which means that these profiles were not a continuous function of the tilt angles, and more tilt angle experiments should be conducted to confirm the continuity of the functions. Furthermore, similar trends were obtained using 3D numerical computation by Sert et al [36], who studied inclined cubical cavities with rectangular pins attached to the hot wall. In their study, the total Nusselt number was found to increase with the Rayleigh number and also to increase with the inclination angle up to a specific angle and then decrease, which agrees with the general trend in Figure 8.…”
Section: Results and Dissuasionsupporting
confidence: 79%
“…It should be noted that the average heat transfer coefficient and Nusselt number profiles shown in Figures 7 and 8 are drawn as dashed lines, which means that these profiles were not a continuous function of the tilt angles, and more tilt angle experiments should be conducted to confirm the continuity of the functions. Furthermore, similar trends were obtained using 3D numerical computation by Sert et al [36], who studied inclined cubical cavities with rectangular pins attached to the hot wall. In their study, the total Nusselt number was found to increase with the Rayleigh number and also to increase with the inclination angle up to a specific angle and then decrease, which agrees with the general trend in Figure 8.…”
Section: Results and Dissuasionsupporting
confidence: 79%